Porous Blasting Morphology and Resistivity Response Characteristics of Soft Coal Seam. (12th August 2022) - Yang, Wenwang; He, Sanlin; Zhao, Taotao; Ge, Chenying
Abstract : The fracturing characteristics of multi-holes blasting in soft coal seam were analyzed quantitatively by using the multi-holes model blasting experiment of soft coal seam and digital image processing (DIP) and electrical resistivity tomography (ERT) techniques, and the electrical resistivity response rules before and after blasting were obtained. The results show the following: (1) At the same time as the formation of blasting-induced cracks, the coal inside the control hole presents two kinds of displacement phenomena: crack and noncrack, partially offsetting the extrusion effect caused by the expansion of the blasting hole. (2) The comprehensive value ( S ) of blasting-induced cracks, control hole, and blasting hole area change is proposed to analyze the blasting effect. When single-hole blasting is performed, S  < 0, the fractal dimension change rate of coal seam crack is only 5%, the control area presents a compaction phenomenon, and the resistivity decreases by about 20%. When multi-hole blasting is performed, the blasting cracks are abundant and the coal displaces sufficiently. The fractal dimension of cracks reaches 21.28%, the negative effect of the blast holes cavity is offset ( S  > 0), and the resistivity in the controlled area generally increases by 1 to 30 times. (3) Compared with the single-hole blasting model, the multi-hole blasting is more in line with the coal mine site, and can effectively increase the permeability in the control area, and the resistivity generally increases.